TAMIL NADU AND INDONESIA FOOD CULTURE: A COMPARATIVE STUDY - Masilalamani, Dr Nirmala; Hermansyah, Dr. Sam; Mohamed S.H, Dr. Sheik; Mothe, Dr.Prashant (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2025)
This study explores the food cultures of Tamil Nadu, India, and Indonesia, focusing on traditional food practices, cultural significance, and social functions. Through a comparative qualitative research approach, this study analyses how food in both regions reflects cultural identity, religious beliefs, and social values. By examining food-related rituals, ingredients, cooking methods, and social customs, this article highlights the ways in which food practices serve as cultural expressions that contribute to community bonding and cultural preservation. The study also examines the impact of globalization on food culture in both Tamil Nadu and Indonesia.